Women Issues Discussed by Feminist Muffasirs in Indonesia - Nabilah Nuraini; Nana Najatul Huda; Eni Zulaiha (UIN Sunan Gunung Djati Bandung, 2021)
The idea of feminism in Indonesia originated in the Dutch colonial period at the end of the 19th century. We saw lots of young women in the struggle against the colonialists. Besides the Idea of Feminism, a movement of Indonesian feminism emerged during the Old Order era named Gerwani (Indonesian Women's Movement), which was founded in the 1950s. The Feminism Movement in Indonesia operates in several ways. Such as organizations, institutions, writings, seminars, and various movements. The beginning of feminist interpretation in Indonesia emerged after Indonesian independence and Islamic education and literature in Indonesia. During the Old Order era, educational facilities and Islamic literature began to be institutionalized, such as the emergence of the State’s Islamic Higher Education (PTAIN) and Islamic University of Indonesia (UII). In Indonesia, the development stage of women ' s interpretation which emerged around the 1960s when Buya Hamka wrote Tafsir Al-Azhar and began to develop rapidly in the1990s with the emergence of several writings by Quraish-Shihab, which were then by several theses and dissertations among Indonesian Muslim intellectuals, which discussed the concepts of the Qur'an. Several feminist mufters in Indonesia, including: Buya Hamka, Quraish Shihab, Husein Muhammad, Mansour Faqih, and other feminist Mufassir figures.